Unearth the Role of Branding towards Customer Satisfaction on Infant Formula Brand in Malaysia: A Critical Review of Enfagrow A+ Mindpro - Arman Hj. Ahmad; Ridzuan Masri; Irbiana Hanim Tahir; Sarah Hazlinda Hazlan; Nurelya Shafika Mohd Sam; Nurul Aziidah Zulkifli; Mohamad Shyafiq Ezzat Yahya (International Journal of Economics, Business and Innovation Research, 2025)
This study is an attempt to critically review and understand the role of branding on customer satisfaction using Enfagrow A+ Mindpro (a brand of Mead Johnson Nutrition, Malaysia) as a case brand. The role of branding on customer satisfaction is of worth significant to know as it is important to make customers satisfy on a specific brand. The elements of branding in Enfagrow A+ Mindpro such as brand image, brand loyalty, brand awareness as well as perceived quality were predicted to contribute to customer satisfaction. Based on the review of past literatures, the customer satisfaction were built up when branding successfully met the needs and requirements of the customers. Contrary to traditional models, this study posits that brand loyalty can precede and influence customer satisfaction, offering a novel perspective on consumer-brand dynamics in Malaysia’s children’s nutrition market. In this review, a research framework is proposed and suggested for future empirical investigations to test the proposed hypotheses. As for the sample of the study, customers who made their purchases of Enfagrow A+ Mindpro brand both in retail and online in Malaysia, will be conveniently targeted as the main population and samples. Data will be collected through a self-administered questionnaire, distributed both in physical form (at retail stores or paediatric clinics) and digitally (via Google Forms shared through parenting networks and vendor mailing lists) which then analysed using a series of statistical procedures using SPSS and AMOS software for the preliminary analyses, Confirmatory Factor Analysis (CFA) to validate the measurement model as well as Structural Equation Modeling (SEM) to simultaneously evaluate the proposed model's fit and assess both direct and indirect paths among variables. The results projected that branding elements will have significant contribution to customer satisfaction towards the brand. The conclusion and implication of the study are discussed to further highlights the initiative. Despite unearthing the connections between branding and customers’ satisfaction, this study advances existing theory by offering a novel framework for understanding consumer-brand relationships in Malaysia’s children’s nutrition market. Furthermore, this paper could enrich the body of knowledge related to consumerism and marketing research.